Water Quality Modelling to Predict BOD And TP Loads of Duriangkang Dam - Wimordi, Calvin; Yudianto, Doddi; Yiqing, Guan (Universitas Indonesia, 2020)
Water quality modeling is highly needed to predict and to identify the water quality alteration and distribution along the water body. Besides that, water quality modeling also can be used to predict the pollutant load if there is no data recording. The water quality analysis simulation program (WASP), will be used in this study to forecast domestic load, in particular BOD and TP loads in Duriangkang Dam. Initially, the estimated load is obtained based on the previous study that being extended by using a linear regression line. After that, the estimated load is calibrated according to the results of the water test. The WASP model is simulated for a period of 3 years from 1 January 2016 to 31 December 2018 and is divided into 2 processes, namely calibration and verification process. The calibration process is carried out in the first two years, followed by the verification process for the remainder of the year. The calibration and verification process are measured by objective functions, namely RMSE and the percentage difference. According to the simulation results, the objective functions provide satisfying findings, which means that the predicted BOD and TP loads for Duriangkang Dam during that time are accurate.